TEORI LIMIT DALAM METODE HUKUM ISLAM MUHAMMAD SYAHRUR - Elkarimah, Mia Fitriah (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2014)
The purpose of this study is know the concept of limit theory according to muhammad Syahrurs?s methodology (here in after referred as: Syahrur). The research findings state that the methodology of Islamic law used by syahrur is diffrent among another convensional?s scholars. He is a technique figure and his also had a very deep interest in the Islamic subjects. He used linguistic approarch, based on this he gave different interpretations of important terms in the Qur'an which led him to formulate his limit theory. The framework on this theory contains two of Islam's main characters (the constant form (Istiqamah) and the flexible form (hanifiyyah), it make Islam's survival, thus enabling the creation and development of the dialectic of the Islamic legal system continuously.The flexibility is in the limit theory refers to the meaning of ?the bounds or restrictions of God which should not be violated, contained in the dynamic?. In addition, Shahrur also used scientific approach. Therefore it is very natural that the theoretical Physics, Mathematics, and Philosophy are affected in his understanding of Islamic law.